Technique optimization of orbital atherectomy in calcified peripheral lesions of the lower extremities. Issue 1 (7th October 2013) - Das, Tony; Mustapha, Jihad; Indes, Jeffrey; Vorhies, Robert; Beasley, Robert; Doshi, Nilesh; Adams, George L.
<x xml:space="preserve">Abstract</x> Objectives The purpose of CONFIRM registry series was to evaluate the use of orbital atherectomy (OA) in peripheral lesions of the lower extremities, as well as optimize the technique of OA. Background Methods of treating calcified arteries (historically a strong predictor of treatment failure) have improved significantly over the past decade and now include minimally invasive endovascular treatments, such as OA with unique versatility in modifying calcific lesions above and below‐the‐knee. Methods Patients (3135) undergoing OA by more than 350 physicians at over 200 US institutions were enrolled on an "all‐comers" basis, resulting in registries that provided site‐reported patient demographics, ABI, Rutherford classification, co‐morbidities, lesion characteristics, plaque morphology, device usage parameters, and procedural outcomes. Results Treatment with OA reduced pre‐procedural stenosis from an average of 88–35%. Final residual stenosis after adjunctive treatments, typically low‐pressure percutaneous transluminal angioplasty (PTA), averaged 10%. Plaque removal was most effective for severely calcified lesions and least effective for soft plaque. Shorter spin times and smaller crown sizes significantly lowered procedural complications which included slow flow (4.4%), embolism (2.2%), and spasm (6.3%), emphasizing the importance of treatment regimens that focus on plaque modification over maximizing luminal gain. Conclusion The OA technique optimization, which resulted in a change of device usage across the CONFIRM registry series, corresponded to a lower incidence of adverse events irrespective of calcium burden or co‐morbidities. © 2013 The Authors. Wiley Periodicals, Inc.